The institutional basis of the systematization and assessment of tourism zones: The case of Uzbekistan: Dasar kelembagaan dari sistematisasi dan penilaian zona pariwisata: Kasus pada Uzbekistan. - Bobur Sobirov (Academia Open, 2019)
This paper investigates systematization and assessment of existing methodological developments in the field of assessing the tourist capacity of territories. Investigated aimed to identify the possibilities of implementing theory of the cluster initiatives on the creating free tourist zones. On this was, evidences from Uzbekistan tourism potential and ways of reaching better attractiveness points of the free tourist zones were mentioned. Finally, research has proposed and suggested to conduct further research points as the whole